The Use of the Jigsaw Method in the Development of Professional Training of Future Teachers - J.O. Baltabaev (Genius Publishing Group, 2023)
This article describes the importance and features of the use of interactive technologies in the process of training future teachers in the higher education system. The content of the jigsaw method, the stages of application, the essence, advantages, conclusions and recommendations are also given.
Keywords: Higher education system; future teachers; interactive methods; jigsaw method